Integration of ESG principles in corporate governance: A review of the latest literature - Hermiyetti, Hermiyetti (International journal of economic perspectives, 2025)
This study aims to analyse the conceptual development and practical implications of integrating Environmental, Social, and Governance (ESG) principles into corporate governance based on the latest literature. The results found that ESG has transformed from a mere compliance instrument to a strategic foundation for creating long-term value and business competitiveness. ESG integration has been proven to improve financial performance, strengthen reputation, and expand access to sustainable capital markets. However, ESG implementation still faces structural challenges, including disparities in reporting standards, infrastructure limitations, and organisational cultural resistance, particularly in developing countries such as Indonesia. The findings of this study emphasise the importance of collaboration between regulators, business actors, and academics in accelerating the adoption of contextual and adaptive ESG. This study also recommends the development of digital-based governance models and a circular economy as future strategies to strengthen corporate sustainability and resilience in an increasingly dynamic business era.